Iniciação à docência na educação básica: professores principiantes e a sua ambiência (trans)formativa - Silva, Weliton Martins da (2018)
This thesis is structured around the theme of insertion into teaching in basic education. It is derived from a qualitative research, taking as context schools of the state network of the city of Sete Lagoas – Minas Gerais. The general objective of the study, with narrative approach, was to understand how the basic education school composed of its different subjects can be configured as a (trans) formative ambience for the insertion of the beginning teacher. The research scenario was composed of 24 schools of the State Education Network of Sete Lagoas - MG that offer the final years of Elementary and High School. The subjects of our research are beginner teachers who have attended the last two public tenders of the State Education System of the State of Minas Gerais (2011 and 2014) for the city of Sete Lagoas, in other words, effective teachers with up to five years of teaching activity. The investigative process began with an exploratory study by means of a questionnaire sent to all the beginning teachers in order to identify the scenarios and the subjects of the research, including questions about the beginning of teaching. The main corpus of the research stems from the teaching narratives, whose content was worked through the Discursive Textual Analysis. The study brought the understanding that the school ambience can promote teacher well-being in the process of professional insertion, motivating him or her to remain in the career. However, it’s possible to verify that the insertion in teaching career requires a combined effort of the different agents responsible for educational policies in regard to training policies - initial and continuous and professional valorization. Finally, the Finally, the thesis is confirmed that the school environment influences the constitution of the identity of the beginner teacher in basic education, being able to constitute a positive or negative environment, being these determinant conditions for the insertion and permanence of these teachers in the teaching activity. It is a matter of priority, to care for the person in the transition phase from student to teacher, to create effective public policies that assure beginner teachers the objective and intersubjective conditions for learning while teaching and for their professional development, in positively welcoming school ambiences.